John Steinbeck and Beatrice Steinbeck - Unknown:::Creator:::::::::::: (Mexico)
John Steinbeck and Beatrice Steinbeck (Stanford's wife) standing, holding Thom by hands. Taken while waiting for beginning of filming for The Pearl/La Perla. John Steinbeck rented this house from his Gwen's relatives who were in the real estate business.